School enrollment effects in a South-South migration context. (September 2018) - Davis, Jason
Highlights: A novel evaluation of the effects of South-South migration on left-behind children's educational outcomes in Latin America. Father's South-South migration is negatively correlated with school enrollment. Higher Hurricane Mitch impact zones are negatively correlated with school enrollment and absence. Abstract: In contrast to the heavily studied South-North migration of Latin Americans to the United States, this investigation assesses the lesser-studied influence of South-South labor migration on left-behind children's educational attainment. Specifically, it asks the question, 'Does the migration of Nicaraguan parents to Costa Rica contribute to better or worse education outcomes for their left-behind children?' Based on migration and education data for 3951 children from 1858 distinct households collected within Nicaragua's 1998 and 2001 Living Standards Measurement Studies, fixed effect model results indicate that paternal migration has a depressive effect on school enrollment but has no effect on school attendance or grade-for-age progression. Given the relatively low bar to migration establishment vis-à-vis the lack of barriers that necessitate significant monetary commitments and time delays, school enrollment results are unexpected.